Projet de loi no 69 — Loi modifiant la Loi de la qualité de l'environnement - Giroux, Lorne (Les Cahiers de droit, 1978)
The following commentary discusses two aspects of Bill 69, an Act to Amend the Environmental Quality Act focusing on the concept of citizen participation as embodied in the Bill and the new environmental impact assesment procedures set up in the proposed amendments. It deplores the fact that, as proposed, the amending act would leave too much discretion with the Minister of the environment in deciding to allow public hearings in the processes. The author also regrets that the important questions relating to the environmental assesment procedure are left to be determined by the rulemaking authority of the government thus thwarting a serious discussion of their scope and seriousness.